2016
DOI: 10.1111/aje.12277
|View full text |Cite
|
Sign up to set email alerts
|

Comparing motion capture cameras versus human observer monitoring of mammal movement through fence gaps: a case study from Kenya

Abstract: Monitoring the movement and distribution of wildlife is a critical tool of an adaptive management framework for wildlife conservation. We installed motion-triggered cameras to capture the movement of mammals through two purpose-built migration gaps in an otherwise fenced conservancy in northern Kenya. We compared the results to data gathered over the same time period (1 Jan 2011-31 Dec 2012) by the human observers monitoring mammal tracks left at the same fence gaps in a sandy loam detection strip. The camera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Despite their limitations, human observations facilitated the collection of rich and numerous data, with the observers able to change their positions to observe the ravens and the cans to ensure that a wide repertoire of behaviours were identified to remediate for aspects that would not be recorded by camera traps alone [27]. In addition to the issue of missing data using the camera trap technology, this methodology is also vulnerable to damage and theft, as was experienced within this study and has been previously reported by Dupuis-Desormeaux et al [19], who stated that camera traps are vulnerable to theft or destruction by poachers or hunters.…”
Section: Study Limitationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Despite their limitations, human observations facilitated the collection of rich and numerous data, with the observers able to change their positions to observe the ravens and the cans to ensure that a wide repertoire of behaviours were identified to remediate for aspects that would not be recorded by camera traps alone [27]. In addition to the issue of missing data using the camera trap technology, this methodology is also vulnerable to damage and theft, as was experienced within this study and has been previously reported by Dupuis-Desormeaux et al [19], who stated that camera traps are vulnerable to theft or destruction by poachers or hunters.…”
Section: Study Limitationsmentioning
confidence: 91%
“…A study carried out by Wearn et al [18] concluded that when comparing camera trap technology to other methods, generally most studies support camera traps as a highly effective tool for surveying wildlife. Camera trap monitoring captures a larger range of species and behaviours compared to human observers that monitor the same areas [19] and has the potential to reduce observer bias, with camera traps allowing for the verification of behavioural scoring and ensuring the consistency of data recordings, provided that the technology is adequately installed [15]. Nevertheless, this technology has limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, manual data collection can miss important information and has time constraints. Therefore, systematic and continuous monitoring is important [ 8 ]. In contrast, many monitoring methods using video cameras [ 9 , 10 , 11 , 12 ] and sensors such as thermography [ 13 ], as well as camera-based behavior analysis have been developed with recent improvements in deep neural network technology [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], making it possible to track animals with high accuracy in a non-contact manner.…”
Section: Introductionmentioning
confidence: 99%
“…Not only has technology reduced time in conducting research, but it has allowed for more accurate collection compared to that of human observers. For example, when Desormeaux and colleagues [6] compared the information collected from motion triggered cameras located at migratory fence gaps to observers' recordings of mammal tracks (e.g., giraffe, zebra, elephant, and hyaena), a higher volume of crossing was reported with technology, suggesting that human observers may often miss important events. Methodologies that use manual collection of data are often time consuming, time limited, and potentially invasive and/or ill-suited depending on the research focus, supporting further investment in the advancement and refinement of technology-based alternatives.…”
mentioning
confidence: 99%